Inovasi Pelayanan Pelaporan Sampah pada Aplikasi Jemput Ragam Sampah (JERAPAH) di Dinas Lingkungan Hidup Kota Cilegon - Ellisa Nursabilla; Hasuri Waseh (Epistemik Press, 2026)
Waste management must be implemented in an integrated and comprehensive manner to address the persistent challenges related to waste accumulation and landfill capacity. Cilegon City, as one of the industrial regions in Banten Province, experienced a significant increase in waste generation during the period of 2022–2023. As the institution responsible for environmental management, the Environmental Service of Cilegon City has introduced various strategies, including the development of an innovation in waste reporting services through the Jemput Ragam Sampah (JERAPAH) application. This digital-based platform enables citizens to report illegal waste (sampah liar) and request the collection of segregated waste efficiently. This study aims to analyze the implementation of public service innovation through the JERAPAH application by applying Rogers’ Diffusion of Innovation theory, particularly focusing on five innovation attributes: relative advantage, compatibility, complexity, trialability, and observability. The research adopts a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The findings indicate that the JERAPAH innovation demonstrates strengths in terms of relative advantage, compatibility, and observability, particularly in improving accessibility, efficiency, and responsiveness of waste management services. However, several challenges remain, especially related to complexity and trialability, such as limited public understanding, technical constraints, and insufficient dissemination of information. These limitations suggest that while the innovation has contributed to improving public service delivery, its implementation has not yet reached optimal performance.